Understanding Basic Music Theory - Schmidt-Jones, Catherine (Open textbook library., 2013)
Although it is significantly expanded from "Introduction to Music Theory", this book still covers only the bare essentials of music theory. Music is a very large subject, and the advanced theory that students will want to pursue after mastering the basics will vary greatly. A trumpet player interested in jazz, a vocalist interested in early music, a pianist interested in classical composition, and a guitarist interested in world music, will all want to delve into very different facets of music theory; although, interestingly, if they all become very well-versed in their chosen fields, they will still end up very capable of understanding each other and cooperating in musical endeavors. The final section does include a few challenges that are generally not considered "beginner level" musicianship, but are very useful in just about every field and genre of music.